A unique stone mould for casting a spearhead from Morkůvky in South Moravia as an example of long-distance import in the Urnfield Period, and its technological contribution - Milan Salaš; Antonín Přichystal; Jan Petřík; Karel Slavíček; Dalibor Všianský; Vojtěch Nosek (Archeologické Rozhledy)
The paper provides a comprehensive analysis of a well-preserved half of a stone mould, accidentally found in the village of Morkůvky (Břeclav District). Although it is a stray find, it is characterised by above-standard informative value from the point of view of both typology and technology, as well as in terms of raw material provenance. According to macroscopic traces and XRF–XRD analyses, bronze was poured into vertically erected halves of the mould, which were tightened with copper wire. The negative reveals that the mould was used to cast a socketed lanceolate spearhead, in which each of the flanking blade wings and the midrib carried a longitudinal rib. This spearhead type is commonly found in the Carpathian Basin and is mostly dated to the Late Bronze Age. The area of its most frequent occurrence thus indicates the Carpathian origin of the mould, which was verified by petrographic analysis. According to its results, the casting mould is made of rhyolite tuff, i.e. a rock that occurs in adequate quantities in northern Hungary. The casting mould from Morkůvky is thus demonstrably the result of long-distance import and further evidence of Carpathian influences in the Middle Danube Urnfield Culture.